2013
DOI: 10.1590/s1806-37132013000300003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an outpatient education program in patients with uncontrolled asthma

Abstract: OBJECTIVE: To evaluate the effects of an outpatient education program in patients with uncontrolled asthma. METHODS: This was an uncontrolled study evaluating an educational intervention and involving patients with uncontrolled asthma ≥ 14 years of age. The participants completed a questionnaire designed to assess the level of asthma control, the inhalation technique, and quality of life. All of the patients underwent pulmonary function testing, after which they participated in an education program consisting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
1
5
0
1
Order By: Relevance
“…Similar to previous studies [2], asthma control level improved after intervention. While in this study, the rate of well-controlled asthma management increased from 13.9% to 77.8% in the intervention group compared with 36.1% to 38.9% in the control group.…”
Section: Asthma Control Pulmonary Function and Quality Of Lifesupporting
confidence: 89%
See 2 more Smart Citations
“…Similar to previous studies [2], asthma control level improved after intervention. While in this study, the rate of well-controlled asthma management increased from 13.9% to 77.8% in the intervention group compared with 36.1% to 38.9% in the control group.…”
Section: Asthma Control Pulmonary Function and Quality Of Lifesupporting
confidence: 89%
“…On the contrary, in an outpatient education program for children with uncontrolled asthma ≥ 14 years of age, FEV1% was proved to be significantly increased [2]. The different characteristics of the participants, the Efficacy of an Asthma Self-management Education Intervention for Children (9-13 Years) with Asthma and Their Caregiver in Wuhan, China 126 small sample size, varying asthma education content and the interval to retest FEV1% may have led to these results.…”
Section: Asthma Control Pulmonary Function and Quality Of Lifementioning
confidence: 92%
See 1 more Smart Citation
“…Asthma control is not difficult to reach target and can be achieved through the design and implementation of a tailored treatment plan that considered the complexity of multiple interrelated factors needed to attain this goal [19,20]. One of the few studies assessed asthma control in Africa, reported a high proportion of patients had inadequately controlled asthma and the factors associated with it were female sex and obesity [21].…”
Section: Discussionmentioning
confidence: 99%
“…Each item has five response choices (each with a score ranging from 1 to 5). Accordingly, the level of asthma control is as follows: controlled (score 20-25), partially controlled (score [15][16][17][18][19], uncontrolled (score <15) [12,16] . The raw score was transformed to range from 0 to 100, with higher scores indicating more asthma control for the purpose of determining its relationship with patients' characteristics.…”
Section: Methodsmentioning
confidence: 99%